Adjustments in timed-artificial insemination protocols without estradiol for Bos indicus - Cavalcanti, Patrícia Rodrigues (2023)
Two experiments were conducted to improve fertility in timed-artificial insemination (TAI) protocols without using estradiol esters (E2) in Bos indicus cows. The first study compared the reproductive efficiency of adjusted TAI protocols with or without E2 and the inclusion or absence of long-acting injectable progesterone (injP4) prior to treatments. Primiparous (n = 293) and multiparous (n = 798) cows, for the first postpartum insemination, were submitted to synchronization protocols, following a 2 × 2 factorial arrangement, resulting in 4 treatments. injP4 + E2 (n = 279), E2 (n = 266), injP4 + GnRH (n = 267) and GnRH (n = 279). Ten d before the beginning of the protocol, the cows were randomly assigned to receive or not 150 mg of injP4. On D0, all cows received an intravaginal P4 device (1 g), concomitantly with the experimental treatments, which were 2 mg of E2 benzoate (E2-based groups) or 16.8 µg of buserelin acetate (GnRH; groups based on GnRH). On D6, cows in the GnRH-based groups received 0.5 mg of cloprostenol sodium (PGF) and 300 IU of eCG. On D7, all cows received 0.5 mg of PGF concomitant with P4 device withdrawal, and cows in the E2-based groups received 300 IU of eCG and 1 mg of E2 cypionate. The AI was performed 48 h later on D9, where all cows received 8.4 µg of GnRH. Ultrasound evaluations were performed on D0, 7, 9, 39, and 69 to assess the diameter of the dominant follicle, CL, ovulatory response after D0, and pregnancy per AI (P/AI). Treatment with injP4, despite increasing follicle size on D0, did not influence the ovulatory response to the first GnRH and had no effect on fertility, regardless of the hormonal basis of the protocol. GnRH-based protocols resulted in lower fertility than E2-based protocols (54.0 vs. 62.4%; P 0.05). However, there was no influence of the hormonal treatments on pregnancy loss. The second study evaluated the luteolytic response to different doses of PGF, using cloprostenol sodium, on 6 and 7 d old corpora lutea (CL). Nelore cows (n = 88) were used, previously synchronized, and were divided into three treatments: Single (n = 30), receiving a regular dose (0.53 mg) on D7; Two doses (n = 29), receiving a regular dose on D6 and another on D7 (both 0.53 mg) and Double (n = 29), receiving a double dose (1.06 mg) on D7. Ultrasound evaluations (D6 D11) and blood collection were performed to assess circulating P4 (D6 D10). Treatment with a single dose of PGF was not sufficient to cause complete luteolysis in all cows; by the end of the evaluations, only 63.3% (19/30) of the cows had undergone luteolysis, while in the other groups, 96.9% (28/29) underwent luteolysis.